2023
DOI: 10.1021/acsorginorgau.3c00001
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of Methane to Methanol via In Situ H2O2 Synthesis

Abstract: The selective oxidation of methane to methanol, using H2O2 generated in situ from the elements, has been investigated using a series of ZSM-5-supported AuPd catalysts of varying elemental composition, prepared via a deposition precipitation protocol. The alloying of Pd with Au was found to offer significantly improved efficacy, compared to that observed over monometallic analogues. Complementary studies into catalytic performance toward the direct synthesis and subsequent degradation of H2O2, under idealized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…These include poor selective H 2 utilization, rapid catalyst deactivation, and the formation of complex product mixtures, necessitating extensive purification and the inclusion of promoters. Indeed, in many cases, it is the presence of H 2 , required to generate H 2 O 2 in situ, that largely promotes the formation of such byproducts. , Such concerns are not limited to alkene epoxidation, with product distributions for a range of transformations influenced by competitive unselective hydrogenation pathways. , It is the overcoming of these challenges that has motivated extensive research from our laboratory, with particular focus placed on the application of Pd-based catalysts for (i) alkane upgrading, (ii) alcohol oxidation, , and recently (iii) the ammoximation of cyclohexanone (and other cyclic ketones) to the corresponding oxime. ,, Regarding alkane oxidation, we direct the reader to our recent Account on methane valorization for an extensive discussion of our contribution to this field …”
Section: Challenging Current Industrial Processesmentioning
confidence: 99%
“…These include poor selective H 2 utilization, rapid catalyst deactivation, and the formation of complex product mixtures, necessitating extensive purification and the inclusion of promoters. Indeed, in many cases, it is the presence of H 2 , required to generate H 2 O 2 in situ, that largely promotes the formation of such byproducts. , Such concerns are not limited to alkene epoxidation, with product distributions for a range of transformations influenced by competitive unselective hydrogenation pathways. , It is the overcoming of these challenges that has motivated extensive research from our laboratory, with particular focus placed on the application of Pd-based catalysts for (i) alkane upgrading, (ii) alcohol oxidation, , and recently (iii) the ammoximation of cyclohexanone (and other cyclic ketones) to the corresponding oxime. ,, Regarding alkane oxidation, we direct the reader to our recent Account on methane valorization for an extensive discussion of our contribution to this field …”
Section: Challenging Current Industrial Processesmentioning
confidence: 99%
“…The development of active materials for this conversion in a high-pressure batch process has been explored on various supported metal sites and metal alloys. Wang and co-workers reported the conversion of methane over oxo dicopper anchored on carbon nitride with a methanol production of 129.7 mmol/g Cu ·h . Hutchings and co-workers reported the production of 7.02 μmol of oxygenates in 30 min of using AuPdCu supported on titania .…”
Section: Introductionmentioning
confidence: 99%
“…Converting methane to methanol is another considerable way to reduce methane gas emission because of its significant cost advantages in transportation and storage. , Converting methane to methanol through partial oxidation at room temperature has remained a challenging issue in catalysis for decades. The CH 4 molecule has a tetrahedral shape, which confers stability and a nonpolar nature. The difficulty arises not only from the strong bonding energy of the C­(sp 3 )–H bond (439 kJ mol –1 ) but also the overoxidation tendency, leading to the formation of CO 2 . Mounting research has suggested H 2 O 2 as an excellent oxidant for converting methane to methanol because of its green oxidation byproduct (water). …”
mentioning
confidence: 99%